2022
DOI: 10.1016/j.sjbs.2021.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Detection of clarithromycin resistance and 23SrRNA point mutations in clinical isolates of Helicobacter pylori isolates: Phenotypic and molecular methods

Abstract: Background and objectives Peptic ulcer disease, chronic gastritis, and stomach cancer are all caused by H. pylori . The most notable drug for the treatment is the antibiotic clarithromycin, which is currently the drug of choice. H. pylori clarithromycin resistance has been associated with point mutations in 23srRNA, the most prominent of which are A2143 and A2144G . In H. pylori bacteria, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…77 A report compared the detection rate of A2144 or A2143 from PCR-RFLP with that of MIC measurement by the agar culture method, and they found that the diagnostic performance was nearly equivalent. 78 Another study compared the diagnostic accuracy of real-time PCR against MIC measurements by culture test, and it showed a high concordance rate; 84.6% of subjects diagnosed with clarithromycin-resistant infections by the culture method also had point mutations in 23S rRNA. 79 DNA gyrase, which is used to break the DNA double helix structure during DNA replication, is required for H. pylori to proliferate.…”
Section: Molecular-based Methodsmentioning
confidence: 99%
“…77 A report compared the detection rate of A2144 or A2143 from PCR-RFLP with that of MIC measurement by the agar culture method, and they found that the diagnostic performance was nearly equivalent. 78 Another study compared the diagnostic accuracy of real-time PCR against MIC measurements by culture test, and it showed a high concordance rate; 84.6% of subjects diagnosed with clarithromycin-resistant infections by the culture method also had point mutations in 23S rRNA. 79 DNA gyrase, which is used to break the DNA double helix structure during DNA replication, is required for H. pylori to proliferate.…”
Section: Molecular-based Methodsmentioning
confidence: 99%
“…Resistance to macrolides has spread to S. pneumoniae and H. influenzae which, as highlighted previously, are on World Health Organisation's priority pathogens list. 145,146 Macrolide esterase (Ere). These enzymes break the ester bond of the macrolide ring to give an inactive linear structure (Scheme 5).…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…Resistance to macrolides has spread to S. pneumoniae and H. influenzae which, as highlighted previously, are on World Health Organisation's priority pathogens list. 145,146…”
Section: Antibacterial Classesmentioning
confidence: 99%
“…The increasing failure rate of eradication treatment due to the appearance of resistant H. pylori strains contributes to the worldwide prevalence of this infection and subsequent inflammatory and neoplastic disorders. Unfortunately, nowadays, the success of this treatment is less than 80% worldwide ( Kocsmár et al, 2021 ; Hussein, Al-Ouqaili & Majeed, 2022 ).…”
Section: Introductionmentioning
confidence: 99%